(untitled) - Robbins, Stephen P (London, 1996)
esigned for one-semester/quarter, undergraduate/graduate-level courses in Organizational Behavior, Organizational Psychology, and Human Relations in departments of management, public administration, psychology, social work, political science, and education. Used by over 600 colleges worldwide, this highly reputable text continues to provide the most comprehensive, reality- based review of organizational behavior of its kind. Fully engaging students with its lively, conversational style, it helps students explain and predict behavior in organizations - pivoting discussions around three levels of analysis: the individual, the group, and the organization system.
Hành vi tổ chức
Keywords: Organizational behavior